Identification and polymorphism discovery of the cathelicidins, Lf‐CATHs in ranid amphibian (Limnonectes fragilis). (25th October 2013) - Yu, Haining; Cai, Shasha; Gao, Jiuxiang; Zhang, Songyan; Lu, Yiling; Qiao, Xue; Yang, Hailong; Wang, Yipeng
<x xml:space="preserve">Abstract</x> To protect themselves against the invasion of microorganisms, amphibians, especially the Rana frogs, are possibly equipped with complex combinations of antimicrobial peptides (AMPs). The two major AMP families, ranid skin secretion AMPs and cathelicidins might together constitute the host innate immune system of amphibians. Cathelicidins are a group of cationic peptides found in leukocytes and epithelial cells, and they play a central role in the early innate immune defense found in virtually all species of mammals. However, they have rarely been reported from amphibians. Here, we report the identification and discovery of polymorphism cathelicidins in Limnonectes fragilis. The expression profile indicated high cathelicidin transcript levels in frog spleen, liver and kidney, but lower levels in lung, skin and stomach. According to the amphibian's unique proteolytic pattern, R125 and L121 of the prepropeptides are predicted to be the processing positions for protease to generate the mature peptides, Lf‐CATH1 and ‐2, respectively. Both consist of 30 amino acid residues, of which two were cysteines positionally conserved among a few known amphibian cathelicidins. Homology modeling analysis revealed that Lf‐CATH1 and ‐2 adopt a tertiary structure with a mostly α helix that is representative of small cationic cathelicidin family peptides. Recombinant Lf‐CATH1 (rLf‐CATH1) was produced in Escherichia coli. Synthetic Lf‐CATH1 and ‐2 displayed potent antimicrobial activities in vitro against a broad spectrum of microorganisms, including standard and clinically isolated drug‐resistant strains, while showing neglectable hemolysis and cytotoxicities.